1996
DOI: 10.1038/nsb0996-782
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rare partially folded molecules in equilibrium with the native conformation of RNaseH

Abstract: Despite the general observation that single domain proteins denature in a completely cooperative manner, amide hydrogen exchange of ribonuclease H in low levels of denaturant demonstrates the existence of two partially folded species. The structures of these marginally stable species resemble kinetic folding intermediates and the molten globule state of the protein. These data suggest that the first region to fold is the thermodynamically most stable portion of the protein and that the molten globule is a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
359
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(370 citation statements)
references
References 25 publications
10
359
1
Order By: Relevance
“…Previous studies showed that RNase H folds in a fast, unresolved burst phase (15 ms dead time) to an intermediate termed "I core " and then much more slowly (in seconds) to the native state (3). HX pulse-labeling and equilibrium native-state HX experiments monitored by NMR showed that I core comprises a continuous region of the protein between helix A and strand 5 and that β-strands 1, 2, and 3 and helix E acquire protection much later, consistent with mutational analysis (2)(3)(4). Single-molecule and mutational studies indicated that the intermediate is obligatory, on-pathway, and folds first even when I core is not observably populated (6,7).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies showed that RNase H folds in a fast, unresolved burst phase (15 ms dead time) to an intermediate termed "I core " and then much more slowly (in seconds) to the native state (3). HX pulse-labeling and equilibrium native-state HX experiments monitored by NMR showed that I core comprises a continuous region of the protein between helix A and strand 5 and that β-strands 1, 2, and 3 and helix E acquire protection much later, consistent with mutational analysis (2)(3)(4). Single-molecule and mutational studies indicated that the intermediate is obligatory, on-pathway, and folds first even when I core is not observably populated (6,7).…”
mentioning
confidence: 68%
“…We used a developing technology, hydrogen exchange pulse labeling measured by MS (HX MS), to study the folding of a cysteine-free variant of Escherichia coli ribonuclease H1 (RNase H), a mixed α/β protein that has served as a major proteinfolding model (2)(3)(4)(5). Previous studies showed that RNase H folds in a fast, unresolved burst phase (15 ms dead time) to an intermediate termed "I core " and then much more slowly (in seconds) to the native state (3).…”
mentioning
confidence: 99%
“…NHX results (Chamberlain et al 1996;Chamberlain & Marqusee, 2000) for the native protein at equilibrium found two subglobal PUFs. In the lowest free-energy PUF strands I, II, III, V, and helix E are unfolded.…”
Section: Ribonuclease H1 (Rnase H)mentioning
confidence: 97%
“…Moreover, entire Ω-loops act as concerted unfolding units (Hoang et al 2002;Krishna et al 2003b), unsurprisingly so, because they are internally packed self-contained structures (Leszczynski & Rose, 1986). β-structures tend to break up into smaller separately cooperative units (Chamberlain et al 1996;Yan et al 2002Yan et al , 2004Bédard et al 2008). …”
Section: Foldon Structurementioning
confidence: 99%
“…Large but still subglobal unfoldings have recently been shown to determine the exchange of some hydrogens in cyt c (Bai et al, 1995;Bai & Englander, 1996), ribonuclease H (Chamberlain et al, 1996), and a hyperthermophilic rubredoxin (Hiller et al, 1997). Exchange by way of large unfolding reactions can be recognized by the sharp dependence of rate on denaturant concentration, which relates to surface exposure in the unfolding reaction.…”
Section: Local Fluctuations and Large Unfoldingsmentioning
confidence: 99%